Chiral Recognition Mechanisms of four β-Blockers by HPLC with Amylose Chiral Stationary Phase - Wang, Dongmei (Shaheed Beheshti University of Medical Sciences, 2014)
The high performance liquid chromatography (HPLC) enantioseparation of four β-blocking agents metoprolol, bisoprolol, propranolol and atenolol was performed on amylose tris-(3,5-dimethylphenylcarbamate) chiral stationary phase using n-hexane-ethanol-diethylamine (DEA) as the mobile phase and related chiral recognition mechanisms were discussed. Enantiomeric separation of the four β-blockers was a result of more than one type of interaction between solutes and CSP. Besides hydrogen bonding, there was another type interaction that was independent of solvent polarity and responsible for enantiomeric selectivity, such as - interactions. Both the groups close to the chiral centers and the substituent groups on the phenyl rings, which were far away from the chiral centers, could contribute to the good separation. The separations of the four β-blocker enantiomers were all enthalpy driven process. In the range of 293–308K (20–35 ℃), as the temperature increased, the retention as well as the resolution decreased. The molecular size rather than concentration of the alcohol modifiers affected the resolution and retention.